Improper Inversion Symmetry Breaking and Piezoelectricity through Oxygen Octahedral Rotations in Layered Perovskite Family, LiRTiO4 (R = Rare Earths). (7th December 2015) - Gupta, Arnab Sen; Akamatsu, Hirofumi; Strayer, Megan E.; Lei, Shiming; Kuge, Toshihiro; Fujita, Koji; dela Cruz, Clarina; Togo, Atsushi; Tanaka, Isao; Tanaka, Katsuhisa; Mallouk, Thomas E.; Gopalan, Venkatraman
Abstract : An improper mechanism for breaking inversion symmetry is revealed and thus inducing piezoelectricity in the family of layered perovskites, Li R TiO4 ( R = rare earths), which are previously reported as centrosymmetric. Noncentrosymmetry in this family of compounds arises from TiO6 octahedral rotation represented by a − b o c o / b o a − c o in the perovskite blocks between R O rock salt and LiO antifluorite layers. X‐ray diffraction and optical second harmonic generation complemented by density functional theory predictions are crucial in determining the new structures. High transition temperature ( T ac ) of up to 1200 K from noncentrosymmetric to centrosymmetric phase is observed. Piezoelectric coefficients ( d 36 ) of up to −15 pC/N are predicted, and piezoelectric force microscopy experiments confirm a piezoelectric response. The demonstrated improper mechanism in this and other layered oxide families, with a wide range of available topologies and chemistries, could aid in the search for high temperature piezoelectrics. Abstract : A new family of piezoelectrics in Ruddlesden–Popper derivative Li R TiO4 ( R = rare earths) layered perovskites is reported. The mechanism for inversion symmetry breaking in this family of compounds is attributed to the oxygen octahedral rotations. The noncentrosymmetric to centrosymmetric phase transition temperatures are ≈800 K and above depending on the size of the rare earth ion.